1999
DOI: 10.1332/251569299x15668906480838
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for Efficiency: User Charges and Municipal Spending

Abstract: User charges have been an increasingly important source of revenue tor local governments. Furthermore, it has been suggested in the public finance literature that user charge finance can increase the efficiency of local government service provision, with the evidence being a reduction of expenditures, ceteris paribus. This paper goes one step further, using an empirical test to distinguishing die quantity effect from the cost effect. An analysis of local sewer service demonstrates that greater reliance on use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Benton (2003b) suggested that modernization of the county structure (adoption of either an appointed administrator-commission type or an elected executive-commission type) could lead to more reliance on user charges and fees because professional managers in modernized counties with home-rule power tend to value administrative efficiency highly, and thus adhere to the benefit-based principle (such as charges and fees) in financing increasing service demands more often than traditional commission-form governments would. Because of the visibility of the consumptionpayment link in user charge financing, the literature (Bierhanzl, 1999;Bierhanzl & Downing, 1998) argues that a properly structured charge pricing system can provide more accurate cost signals, enabling consumers to properly evaluate the service, discouraging excessive or wasteful consumption of the service (efficiency gain). However, Benton did not empirically test whether professional managers in modernized counties rely more heavily on user charges collection.…”
Section: Literaturementioning
confidence: 99%
“…Benton (2003b) suggested that modernization of the county structure (adoption of either an appointed administrator-commission type or an elected executive-commission type) could lead to more reliance on user charges and fees because professional managers in modernized counties with home-rule power tend to value administrative efficiency highly, and thus adhere to the benefit-based principle (such as charges and fees) in financing increasing service demands more often than traditional commission-form governments would. Because of the visibility of the consumptionpayment link in user charge financing, the literature (Bierhanzl, 1999;Bierhanzl & Downing, 1998) argues that a properly structured charge pricing system can provide more accurate cost signals, enabling consumers to properly evaluate the service, discouraging excessive or wasteful consumption of the service (efficiency gain). However, Benton did not empirically test whether professional managers in modernized counties rely more heavily on user charges collection.…”
Section: Literaturementioning
confidence: 99%